Rancang Bangun dan Uji Kinerja Mesin Bead Roller untuk Perbaikan Bodi Kendaraan - Wisnujati, Andika; Yusuf, Mirza (Universitas Trunojoyo Madura, 2021)
In developing the 4.0 industrial revolution era, vehicle body repair manufacturing companies are required to carry out technological innovations to support effective and efficient performance. One way is in the metal forming process, namely by changing the metal's shape into a variety of products by the company to increase the selling value of the material. The method of forming metal or these materials uses a bead roller machine with a compressive force to carry out the forming process on sheet metal plates according to the size of the tools' geometry and shape. The design of this bead roller machine is operated by using an electric motor with a power of 0.5 HP, using an Alternating Current (AC) voltage, the thickness of the iron frame dimensions of 1.2 cm, and using a reducer with a ratio of 1: 100. Selection of engine parts such as shafts, bearings, tools, and sprockets using materials that are economical and easy to obtain. The design uses Autocad 2014 Software, starting with designing a bead roller machine design paying attention to the strength of the materials used, then assembling the components and the machine's electrical system. The result of this design will be displayed by performing the bead roller machine performance. This bead roller can increase work productivity efficiently and effectively concerning sheet metal media for vehicle body repair compared to manual roll bending tools.